Network positions: Strategic Alliance in the Tobacco Industry in Nicaragua - Gómez García, Reynaldo (Centro Universitario Regional de Estelí. UNAN-Managua/CUR-Estelí, 2014)
This paper is based on the theory of the organizations as a network. I study the strategic alliances in the tobacco industry in Nicaragua. The study is more theoretical than empirical. I work with approaches in this field and any data of Central Bank of Nicaragua. My objective is to demonstrate that the firms in the tobacco industry are prone to enter in strategic alliances.Keywords: Network Positions, Strategic Alliances, crowding positions, Tobacco Industry.